Iberian America in the Spanish teaching of History (Práxis Educativa, 2013)
From the nineteenth century to the present day, since the implementation of the liberal educational system, Iberian American countries have been permanently discussed in textbooks of Spanish secondary education. This attention is traditionally given in both manuals dedicated to the history of Spain and in those that approach the so-called universal history, so defined despite its marked Eurocentric form. This continued presence of Iberian American countries have, however, different levels of intensity according to the time of the publication, in the sense of historical contents related to these historical processes having greater or lesser space in the pages of manuals: that is the issue we cover in detail in our investigation.Keywords: Iberian America. History teaching. School manuals.